Vegetative Propagation of Dendrocalamus strictus through Macro-proliferation - Kumar, Adarsh; Gupta, B. B.; Negi, D. S. (Indian Forester, 1988)
Tbe propagation of Dendrocalamus strictus through seedling proliferation has been studied. It has been found that the mother stock of seedlings can be multiplied four to six times depending on fertiliser application in a period of eight months. The proliferated seedlings are easy to handle and transport as they remain small in size due to continuous rhizome separation. A methodology for multiplication of seedlings has been developed for D. strictus and is reported here.